A new colour image encryption approach using a combination of two 1D chaotic map. (23rd July 2020) - Herbadji, Djamel; Derouiche, Nadir; Belmeguenai, Aissa; Tahat, Nedal; Boumerdassi, Selma
In this paper, we propose an improved chaotic map by coupling two existing methods. Numerical tests prove that the proposed technique presents closely complex behaviour and wider chaotic range than their seed maps. In this paper a new colour image encryption approach using the enhanced chaotic map has been suggested. The proposed scheme is based on the conventional confusion-diffusion structure that contains a new permutation process, it has designed to randomly scramble neighbouring pixels. The performance and the quality measurement of the proposed scheme are analysed by comparing it with some existing research.